Mutual Relationship between Human and Nature on The Secret Garden and Sarongge: an Ecocritical Reading - Ignadhitya Herdiana; Eva Najma (Vivid: Journal of Language and Literature, 2019)
This article aims to show the mutual relationship between humans and nature that influence to heal mental and physical of human that shown on The Secret Garden written by Frances Hudgson Burnett and Sarongge by Tosca Santoso. The mutual relationship described by the two authors is also related to social events and natural conditions in the early 20th century in England and early 21st century in Indonesia. We might realize that the main function of literature is not only to entertain but also to teach us how important nature to humans. In this case, the researchers use qualitative methods and apply eco-criticism to explain how close the relationship between nature and humans in the novels. Using these English and Indonesian novels, the researchers criticize how human behavior preserves the nature that is present in both novels and compared to the reality that occurs. The findings is it reflects the mutual relationship between humans and nature that can heal mental and physical. However, it is irrelevant to the reality with the history of the environment that occurs is excessive exploitation of nature and has a negative impact on humans. Hereby builds the reader's awareness of the importance of nature for human survival, especially on mental and physical health.